Simulation of dosimetric consequences of intrafraction variation of tumor drift in lung cancer stereotactic body radiotherapy - Han, Bin; Wu, Bian; Hu, Fala; Ma, Yangguang; Wang, Haiyang; Han, Xinwei; Liu, Gang; Guo, Yuexin (Frontiers in Oncology, 2022)
The purpose of this study was to investigate the target dose discrepancy caused by intra-fraction variation during stereotactic body radiotherapy (SBRT) for lung cancer. Intensity-modulated radiation therapy (IMRT) plans were designed based on average computed tomography (AVG CT) utilizing the planning target volume (PTV) surrounding the 65% and 85% prescription isodoses in both phantom and patient cases. Variation was simulated by shifting the nominal plan isocenter along six directions from 0.5 mm to 4.5 mm with a 1-mm step size to produce a series of perturbed plans. The dose discrepancy between the initial plan and the perturbed plans was calculated as the percentage of the initial plan. Dose indices, including ΔD99 and ΔD95 for internal target volume (ITV) and gross tumor volume (GTV), were adopted as endpoint samples. The mean dose discrepancy was calculated under the 3-dimensional space distribution. We found that motion can lead to serious dose degradation of the target and ITV in lung SBRT, especially during SBRT with PTV surrounding the lower isodose line. This phenomenon was compromised when 3-dimensional space distribution was considered. This result may provide a prospective reference for target dose degradation due to motion during lung SBRT treatment.